Sistem Monitoring dan Logging pada Oxygen Concentrator Berbasis Node-RED dengan Protokol MQTT - Keyasa Abimanyu Nugroho; Dian Figana (Jurnal Arus Elektro Indonesia, 2023)
Covid-19 is a spreading disease caused by SARS-CoV-2, a type of coronavirus. Covid-19 first case was reported from Wuhan, China on 31 December 2019. The virus spread rapidly to the other countries all over the world. The virus spread from an infected person’s mouth or nose in small liquid particles when they cough or sneezing. Oxygen supply in Indonesia is rare because everybody’s panick to buy their own oxygen tank and refill the supply. With PSA technology, Oxygen Concentrator that is going to be made will have an Oxygen Concentration output more than 90%. This sistem is using VPS that has its own public IP that can be accessed by internet. Monitoring and Logging system is made using flow on Node-RED that will monitor data from PLC, Oxygen Concentration and Flow. PLC Data that is read-able by Node-RED LocalHost will be published to broker using MQTT. The othe Node-RED VPS will subscribed to the broker with a specific topic and get that data. Based on the tests that is done, the monitoring and logging system is working, it shows the data on a gauge widget, chart, and level. The data that is sent through broker will be stored in a database. The data will be called by query if the user wanted to see the logger data based on the date. The maximum value of the measured Oxygen Concentration is 96.18%.